The Influence of Accounting Information Quality, Accountability and Transparency on Zakat Receipt - Dewi Purnama Sari; Siti Atikah; Nur Fitriyah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This study aims to analyze the effect ofquality of accounting information, accountability and transparency of financial reporting on the receipt of zakat. This research is an associative researchThe data used in the form of primary data by distributing questionnaires to amil and muzakki from the National Zakat Agency (BAZNAS) in West Manggarai Regency. 99 questionnaires were distributed, but 90 were collected and can be studied.Analysis of data to test the hypothesis used multiple linear regression with analysis the SPSS program.The result of the study stated that the quality of accounting information and Transparency has positive affect the receipt of zakat in the BAZNAS of West Manggarai Regency. On the contrary, accountability to have no effect on the receipt of zakat in the BAZNAS of West Manggarai Regency.Keywords :the quality of accounting information, accountability, transparency, the receipt of zakat.